2016
DOI: 10.7314/apjcp.2016.17.3.1499
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Crocin Induced Caspase Mediated MCF-7 Cell Death: In Vivo Toxicity Profiling and Ex Vivo Macrophage Activation

Abstract: Background: Crocus sativus and its major constituent crocin are well established to have anti-cancer properties in breast cancer cells (MCF-7). However the role of C. sativus extract (CSE) and crocin on caspase signaling mediated MCF-7 cell death at molecular level is remains unclear. In this study, we tried to unravel role of CSE and crocin on caspase mediated MCF-7 cells death and their in vivo preclinical toxicity profiling and immune stimulatory effect. Materials and Methods: CSE extract was fractionated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 37 publications
1
16
0
2
Order By: Relevance
“…The exact mechanisms how crocin increases microglial phagocytosis are currently unknown. However, crocin-treated peritoneal mouse macrophages also showed increased yeast phagocytosis, corroborating our data [23] .
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…The exact mechanisms how crocin increases microglial phagocytosis are currently unknown. However, crocin-treated peritoneal mouse macrophages also showed increased yeast phagocytosis, corroborating our data [23] .
Fig.
…”
Section: Resultssupporting
confidence: 91%
“…It has also been demonstrated that crocin reduces DNA damage and cell necrosis and prevents the death of PC‐12 cells through sphingomyelinase‐ceramide signaling by enhancing glutathione synthesis (H. Hosseinzadeh, Abootorabi, & Sadeghnia, ; Ochiai et al, ). In addition, several reports showed that crocin has different properties on clinical and metabolic disturbance including increases in mRNA and brain‐derived neurotrophic factor, protein status of VGF neuropeptide, cAMP response element binding (Dorri et al, ; Razavi et al, ), downregulation of mitogen‐activated protein kinase, mitogen‐activated protein kinase‐activated protein signaling pathway, miRNA‐122 expression (Vahdati Hassani, Mehri, Abnous, Birner‐Gruenberger, & Hosseinzadeh, ), inhibiting apoptosis (Razavi, Hosseinzadeh, Abnous, Khoei, & Imenshahidi, ), decreased TNF‐α and IL‐6 levels in striatum (L. Mohammadzadeh, Hosseinzadeh, Abnous, & Razavi, ), modulates IL‐4/IL‐13 signaling (Yosri, Elkashef, Said, & Gameil, ), inhibiting TAU protein hyperphosphorylation, and antiapoptotic effects (Leila Mohammadzadeh, Abnous, Razavi, & Hosseinzadeh, ), alteration of gene expression profile of T24 (transitional cell carcinoma of bladder) cell (Lv, Luo, Ji, & Zhao, ), and regulate the expression of Bcl‐2 with simultaneous up regulation of pro apoptotic Bax in MCF‐7 cells (Bakshi, Hakkim, & Sam, ).…”
Section: Discussionmentioning
confidence: 99%
“…As per the WHO, dietary herbs and their constituents are highly tolerable by the human system compared to synthetic products. Our previous study showed that 300 mg/kg of body weight of C. sativus extract administration to normal mice is safe and there was no adverse histopathologic differences observed in the major organs [ 35 ] . The extent of lung fibrosis during metastasis correlated with lung collagen hydroxyproline content because during lung fibrosis, collagen is deposited massively in the alveolus of the lungs.…”
Section: Discussionmentioning
confidence: 99%